An empirical method for determining the mechanical properties of jointed rock mass using drilling energy. (April 2019) - He, Mingming; Li, Ning; Zhang, Zhiqiang; Yao, Xianchun; Chen, Yunsheng; Zhu, Caihui
Abstract: Characterization of jointed rock masses and evaluation of their mechanical properties are challenging tasks in rock engineering. This paper presents an experimental investigation of the response characteristics of drilling energy to the discontinuity of rock mass using a drilling method. The linear relationship between the drilling energy and discontinuity frequency is revealed, which only depends on the rock type, and is independent of calculation units. A new empirical method for determining the rock quality designation (RQD) versus the variation of drilling energy is proposed based on the discontinuity frequency. Comparison between the prediction and in situ investigation results demonstrates that the RQD can be estimated from this empirical method. The E m / E r (modulus ratio) and σ cm / σ c (strength ratio) versus RQD relations are modified for the determination of rock mass strength and deformation modulus in order to consider the continuous variation of E m / E r and σ cm / σ c with the model parameter η, which is related to the drilling energy and modulus of elasticity of intact rock and the variation of drilling energy for rock mass. The results show that the modified E m / E r ( σ cm / σ c ) versus RQD relations can give proper values compared with the field test results as well as compared with the various proposed relations from RMR, Q and GSI. The modified relations can provide a practical, fast and easy-to-use method for the estimated rock mass strength and deformation modulus, but they are only a first approximation.